Bilingualism: it’s Impact on Assamese Society (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Bilingualism and multilingualism mainly deal with the use of different languages in a society, state or country. Bilingualism is a linguistic community sharing more than one language and their functional allocation. In bilingual societies, different languages and varieties often serve different functions. For example, in Assam, English is used in science and technology, international trade and higher level academic transactions, whereas the Assamese language is used mainly in religion and social gatherings. In other words, English is used as a language of modernization and Assamese is used as a language of intimacy. English and Assamese languages play a complimentary role in Assamese society.Keeping this background in mind, this research paper tried to find out the status of English language in Assam as a multilingual state. The purpose of this paper is to study how English words and expressions find their way in day-to-day conversations of the Assamese people.